Implemetation HOTS Based-Learning During Covid-19 Pandemic in Indonesian Elementary School - Fatimahtuzzahroh, Annis Maulia; Mustadi, Ali; Wangid, Muhammad Nur (FKIP Universitas Lampung, 2021)
Implementation HOTS Based-Learning during Covid-19 Pandemic in Indonesian Elementary School. Objective: This research aims to describe the learning process oriented HOTs in midst of the Covid-19 pandemic outbreak. Method: This research is a qualitative research with phenomenological research type. The data was collected by phone interview to 17 elementary school teachers in Central Java Province. Data analysis is using Bogdan & Biklen models. Findings: The results showed that the application of HOTs-based learning during pandemic: 1) teacher’s knowledge of HOTS learning is quite good, 2) planning of HOTS-based learning process is still not optimal, 3) HOTs-based learning process has not been carried out to the maximum, 4) In the evaluation activities of HOTS-based learning is still relatively low , and 5) Many obstacles faced during HOTS-based learning process. Conclusion: HOTs-based learning during the Covid-19 pandemic cannot be done to the maximum although there are teachers who have tried to implement it in accordance with their knowledge.Keywords: HOTs-based learning, Covid-19 pandemic, elementary school. DOI: http://dx.doi.org/10.23960/jpp.v11.i1.202109